Manfaat Interaksi Teman Sebaya Terhadap Perilaku Sosial Anak Usia Dini Di Ra Muslimat Nu 007 Gandu 1 Mlarak Kabupaten Ponorogo Provinsi Jawa Timur - Farida, Nuning; Friani, Devi Anggi (Universitas Merdeka Madiun, 2018)
To create a good social environment for children, peers are needed, because peers have an important role in creating a social environment that supports the development of children's social behavior. In life among peers there is a social process in which processes influence and influence each other. This research is a descriptive qualitative study, data obtained by observation, in-depth interviews, and documentation. The validity of the data technique uses triangulation techniques. Analysis of qualitative data is carried out interactively and takes place continuously until complete, so the data is saturated. Activities in data analysis are data reduction, data display, and conclusion drawing / verification